Design And Experimental Verification Of Mesh Type Radio Network For Nonlicensed Band - Váňa, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
With growing penetration of Internet, people are trying to find new ways of how to use it for better comfort of themselves. One of the new ways of using the Internet are IoT technologies, which are connecting our cars, our houses and our cities. This paper focuses on designing and experimental verification of such IoT, wireless, MESH technology. There are many solutions on the market for this purpose, but this paper is focused on IQRF technology. It elaborates theoretical basis for IQRF and simple design of topology. The main output is to have the topology tested in real life conditions and to verify the theoretical data plus make first evaluation of the possibilities of IQRF.
Keywords: IQRF; IoT; MESH; Cloud